The Study of Mathematical Reasoning Using Cooperative Learning Among Grade 4 Students Darasamut Phuket School - ลำโป วานีตา; จิรวัตรพาณิช อนุวัตร; ชูจันทร์ จุฑามาศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to study mathematical reasoning, changes in mathematics achievement before and after the learning management, and participation behavior, enthusiasm and responsibility of learners of Grade 4 students using cooperative learning management. The target group was 36 Grade 4 students in the second semester of the academic year 2024. Purposive selection was used. The research instruments included 1) 8 mathematics lesson plans on decimals; 2) Pre-test and post-test on decimals in the form of 20 multiple-choice questions with 4 options; 3) Mathematical reasoning measurement and evaluation form; and 4) Participation and enthusiasm observation form. Data were collected in the second semester of the academic year 2024. The research data included data from pre-post tests, data from mathematical reasoning assessment forms, and data from participation behavior observation forms. Content analysis and descriptive analysis were used. The research results found that the results of the study of mathematical reasoning on decimals by cooperative learning management for grade 4 students, the target group of students had a good result in mathematical reasoning on decimals by cooperative learning management for grade 4 students, which was in line with the predicted hypothesis. The academic achievement by cooperative learning management on decimals of grade 4 students found that 36 students in the target group passed the academic achievement test. The academic achievement before learning about decimals had a mean of 7.97, with a standard deviation of 2.69, and the academic achievement after learning about decimals had a mean of 16.00, with a standard deviation of 2.44. The results of the evaluation of the participation behavior, enthusiasm, and responsibility of students while learning by cooperative learning management on decimals of grade 4 students found that the target group of students had participation behavior, enthusiasm, and responsibility through the specified criteria, with an average score of 2.11, which is at a good level, passing the specified criteria.